RUPTURED ECTOPIC PREGNANCY PRESENTING AS ACUTE APPENDICITIS WITH A FALSE NEGATIVE URINE PREGNANCY TEST IN A LIMITED RESOURCE SETTING: A CASE REPORT - Nooryanto Mukhamad; Rony Sibuea (Yayasan Pendidikan Medika Indonesia, 2026)
Preterm Premature Rupture of Membranes (PPROM), defined as the rupture of membranes before 37 weeks of gestation, can lead to serious complications such as infection. Vaginal probiotics have the potential to serve as a solution by restoring a healthy microbiome balance while reducing the risk of antibiotic resistance when used as adjunctive therapy. This study aims to investigate the effects of vaginal probiotics in normalizing the vaginal microbiota of pregnant women as prophylaxis for PPROM. A review of four Randomized Controlled Trial (RCT) articles from databases such as Google Scholar, PubMed, and ScienceDirect up to January 2025 evaluated the effectiveness of probiotics. The quality of the studies was assessed using the Joanna Briggs Institute (JBI) checklist. Three studies showed that probiotics were effective in improving pregnancy outcomes. One study reported that oral probiotics in healthy pregnant women may reduce the incidence of PPROM. Consistently, probiotic administration was associated with significant improvements, including an increase in gestational age at delivery (ranging from 30.18±2.49 to 34.0±2.0 weeks) and an increase in infant birth weight (from 1,562±450 g to 2,800±440 g). The length of stay in the neonatal intensive care unit (NICU) was also shorter in the probiotic group. It can be concluded that vaginal probiotics, especially when used in conjunction with antibiotics, provide significant benefits as prophylaxis for PPROM and contribute to improved maternal and neonatal health.